Relationship between overexpression of ras p21 oncoprotein and K-ras codon 12 and 13 mutations in Turkish colorectal cancer patients - Mustafa AKKİRPİK and Çiğdem Ataizi ÇELİKEL and Fikret DÜŞÜNCELİ and; r SÖNMEZ and; dır M. GÜLLÜOĞLU and; n SAV and; ÖZER (Turkish Journal of Gastroenterology, 2019)
-